PENGARUH MEDIA INTERAKTIF WORDWALL TERHADAP HASIL BELAJAR RANAH KOGNITIF SISWA PADA MATA PELAJARAN IPAS - Fazira, Cindy; Sulistri, Emi; Zulfahita, Zulfahita (Universitas Muhammadiyah Makassar, 2025)
This study aims to determine whether the use of Wordwall interactive media has an effect on student cognitive learning outcomes in IPAS subjects. The type of research used is quantitative research with quasi experiments method. The research design used was nonequivalent control group design. The population in this study were fourth grade students at SDN 1 Singkawang. The research sample was grade IV students who were divided into two groups, namely the experimental group using Wordwall interactive media and the control group with conventional learning models. The prerequisite test carried out is a normality test using the Chi-squared formula and a homogeneity test is carried out to see the similarity of variants in the two groups. For hypothesis testing, independent sample t-test was used. The results showed that from the results of the calculation of the learning outcomes of the experimental class and control class using the independent sample t-test test showed that , namely 6.678 2.008, meaning that was rejected and was accepted, so that there was a difference, it could be concluded that there was an effect of Wordwall interactive media on student cognitive learning outcomes in IPAS subjects.Keywords: Interactive Media, Wordwall, Learning Outcomes, IPAS